Análisis Técnico- Económico del Sistema Productivo de Bioplastificante Cubano para la Producción de Hormigón - Lorenzo Machado, Yudith (Universidad Central "Marta Abreu" de las Villas, 2014)
The plasticizer additives nowadays are compose indispensable in the industry of the concrete, in our country the additives that are used are concerned, which implies stops costs for the country and cost in currencies. The product substitution concerned by additives of national production with similar characteristics and quality makes possible to insert to us in the very sensible present markets to the changes of the surroundings and for the Cuban industry greater product of the blockade economic imposed to our country constitutes an uncertainty. The development of new products using technology of Efficient Microorganisms implies the design of production systems that from the availability of resources manage to satisfy the demand of market. In the present investigation a study takes place that allows making a technical analysis economic to produce MEF 32 in the Technological Institute “Carlos J. Finlay” that can be very useful for the process from strategic planning and the decision making for the organization.
Keywords: Análisis Técnico- Económico de MEF 32; Tecnología de Microorganismos Eficientes; Instituto Tecnológico Carlos J. Finlay; Analysis